2014
DOI: 10.1371/journal.pone.0089188
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genotyping of Anisakis Larvae in Middle Eastern Japan and Endoscopic Evidence for Preferential Penetration of Normal over Atrophic Mucosa

Abstract: BackgroundAnisakiasis is a parasitic disease caused primarily by Anisakis spp. larvae in Asia and in Western countries. The aim of this study was to investigate the genotype of Anisakis larvae endoscopically removed from Middle Eastern Japanese patients and to determine whether mucosal atrophy affects the risk of penetration in gastric anisakiasis.MethodsIn this study, 57 larvae collected from 44 patients with anisakiasis (42 gastric and 2 colonic anisakiasis) were analyzed retrospectively. Genotyping was conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 24 publications
0
38
1
Order By: Relevance
“…In Japan, A. simplex s.s. is the most important etiological agent as reported that 84 out of the 85 patients (98.8%) were infected with A. simplex s.s. while one patient (1.2%) infected with A. pegreffii (Umehara et al, 2007). Recently, 57 larvae collected from 44 patients with anisakiasis from Middle Eastern Japan were analyzed retrospectively and nearly all larvae were A. simplex s.s. (99%) while one larva displayed a hybrid genotype (Arai et al, 2014). A. simplex s.s. larvae have the potential to survive acidic gastric juice to some extent and penetrate the stomach, small intestine, or colon in infected humans (Arizono et al, 2012).…”
Section: Localitymentioning
confidence: 99%
“…In Japan, A. simplex s.s. is the most important etiological agent as reported that 84 out of the 85 patients (98.8%) were infected with A. simplex s.s. while one patient (1.2%) infected with A. pegreffii (Umehara et al, 2007). Recently, 57 larvae collected from 44 patients with anisakiasis from Middle Eastern Japan were analyzed retrospectively and nearly all larvae were A. simplex s.s. (99%) while one larva displayed a hybrid genotype (Arai et al, 2014). A. simplex s.s. larvae have the potential to survive acidic gastric juice to some extent and penetrate the stomach, small intestine, or colon in infected humans (Arizono et al, 2012).…”
Section: Localitymentioning
confidence: 99%
“…are the causative agents of human anisakiasis and pseudoterranoviasis, respectively (Ishikura and Kikuchi, 1990;Daschner et al, 2012;Nieuwenhuizen, 2016). Among the species of Anisakis so far genetically characterized (Mattiucci and Nascetti, 2008;Mattiucci et al, 2009), only A. pegreffii and A. simplex (s. s.) have been documented to cause infections in humans (D'Amelio et al, 1999;Umehara et al, 2007;Fumarola et al, 2009;Moschella et al, 2004;Mattiucci et al, 2011Mattiucci et al, , 2013Qin et al, 2013;Arai et al, 2014;Lim et al, 2015). Among the species of the genus Pseudoterranova so far genetically characterized (Mattiucci and Nascetti, 2008;Timi et al, 2014), human cases of pseudoterranoviasis are reported as inflicted by P. azarasi (Arizono et al, 2011) and P. decipiens (s. s.) (Cavallero et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A. pegreffii is not the only species able to cause human anisakiasis. In Japan, Umehara et al [ 14 ] and Arai et al [ 15 ] recognized A. simplex (s .s.) as the main etiological agent of anisakiasis in a large number of patients.…”
Section: Resultsmentioning
confidence: 99%
“…A. pegreffii is the most widespread anisakid species affecting commercial fish from Mediterranean waters; its geographical distribution includes the Iberian Atlantic coast waters, as well as the Atlantic and Pacific Austral waters [ 7 , 8 ]. Indeed, so far A. pegreffii is reported as causative agent of invasive anisakiasis in Europe (Italy, Croatia) [ 9 – 13 ], but also in Japan [ 14 , 15 ] and South Korea [ 16 ]. It has been demonstrated with molecular markers that A. pegreffii is able to cause gastric [ 9 , 10 , 12 , 14 16 ], intestinal [ 11 , 13 ] anisakiasis and gastroallergic anisakiasis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%